Are twin currency and debt crises special? - Bernhard Herz; Christian Bauer; Volker Karb (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
We show theoretically and empirically that twin currency and debt crises should be treated as a particular crisis type. Twin currency and debt crises differ from both pure currency and pure debt crises in their determinants, the course of the crises, and their economic consequences. We find that each crises type has a unique set of macroeconomic causes. We also uncover internal contagion and selection bias effects which may lead to biased results if twin crises are not treated separately. Such a separation considerably improve the efficiency of early warning systems especially on debt and twin crises.
Keywords: 330